Using YouTube Content as A Supplementary Instructional Media for Economics Subject of Senior High School - Choirunnisa, Luthfi Alif Dinar (Unversitas Negeri Malang, 2019)
This research aims at observing and describing the utilization of YouTube as instructional media for Economics subject of senior high school. This research was conducted by employing a case study approach to reveal the phenomena. The research was conducted at SMAN 1 Pacitan East Java. The subjects of the research were teachers of Economic subject and students at SMAN 1 Pacitan. The data were obtained through direct observation, documentation, and literature review. The results indicated that the utilization of YouTube as instructional media is effective to motivate studentsâ€™ learning. It is proven by the active participation and enthusiasm of students during the learning process. However, during the implementation of Economics subject lesson with the utilization of YouTube, several constraints were found. The constraints were the quality of video uploaded, the connection of internet, and internal self-regulation of students in accessing YouTube. This research suggests to the teacher to be able to master YouTube as instructional media to create an attractive learning process. In addition, the future research could extend the research by developing more variety of instructional media that can be integrated by YouTube.Â Keywords:Â Youtube content as learning, learning media, economic subject